DEVELOPMENT OF PUBLIC MEDICAL CARE FOR CHILDREN AND ADULTS IN CARPATHIAN REGION (END OF THE XIX - THE FIRST HALF OF THE XX CENTURY) - Bilavych, Ivan; Pantyuk, Mykola; Slyvka, Larysa (Mountain School of Ukrainian Carpaty, 2019)
During the investigated period, the terms like «care», «public care», «medical care» and similar were actively used by doctors, public activists, educators, religious figures, which proves the existence of such a phenomenon, understanding of its importance to the Ukrainian community. The idea of public medical care had been developed amongst Ukrainian scientific, educational, and public circles of Halychyna from the end of the 19th century to 1939; the theoretical assets of scientists were actively implemented in the practical life of locals. The key notion of public (social) medical care is used in the following ways: voluntary care of public institutions about the health of the Ukrainian population of Halychyna, medical care for children and adults, treatment and prevention of diseases, constant supervision and control of health preservation of personality, etc. It is proved that such preconditions and factors as liberal character of domestic policy of the Austro-Hungarian monarchy, the reformation of education and health care systems, creation of a legislative framework for the activities of public associations, etc., have become an important basis for the self-organization of Ukrainians, Ukrainian national movement development, creation of the first Ukrainian medical societies, the birth of Ukrainian science, emergence of a cohort of outstanding figures in the medical sphere (I. Horbachevskyi, Ye. Ozarkevych, S. Okunevska-Morachevska, Ya. Okunevskyi, etc.), institutionalization of Ukrainian public health care in the form of medical, scientific, charitable and other community initiatives (Society of Galician Physicians, Medical Commission of Shevchenko Scientific Society, Medical Community, Lviv Polyclinic, «Narodna Litchnytsya», ULT, UHT, etc.). The article analyzes the achievements of local doctors and scientists in the process of formation of Ukrainian medicine. We give a brief description of contribution of K.Voievidka, V.Yanovych, O.Malaniuk, Ye.Ozarkevych, Ya. Okunevskyi, R. Yarosevych and others doctors. Methodological basis of the research are leading positions of the theory of scientific knowledge, system-structural and cultural approach as a methodological way of studying of educational phenomena and pedagogical processes. The author applied anthroposophic approach that gave a reason to interpret this phenomenon through the prism of values, knowledge and norms of behavior.